Inside the 8p23.1 duplication syndrome; eight microduplications of likely or uncertain clinical significance. (11th June 2015) - Barber, John C. K.; Rosenfeld, Jill A.; Graham, John M.; Kramer, Nancy; Lachlan, Katherine L.; Bateman, Mark S.; Collinson, Morag N.; Stadheim, Barbro Fossøy; Turner, Claire L. S.; Gauthier, Jacqueline N.; Reimschisel, Tyler E.; Qureshi, Athar M.; et al.
<x xml:space="preserve">Abstract</x> The 8p23.1 duplication syndrome (8p23.1 DS) is a recurrent genomic condition with an estimated prevalence of 1 in 58, 000. The core 3.68 Mb duplication contains 32 genes of which five are currently candidates for the phenotypic features. Here we describe four patients and five families with eight microduplications of 8p23.1 ranging from 187 to 1082 kb in size and one atypical duplication of 4 Mb. These indicate that a minimal region of overlap (MRO) in medial 8p23.1 can give rise to features of 8p23.1 DS including developmental delay, dysmorphism, macrocephaly and otitis media, but not congenital heart disease (CHD). This MRO spans 776 kb (chr8:10, 167, 881–10, 943, 836 hg19) and contains SOX7 and seven of the other 32 core 8p23.1 DS genes. In centromeric 8p23.1, microduplications including GATA4 can give rise to non‐syndromic CHD but the clinical significance of two smaller centromeric microduplications without GATA4 was uncertain due to severe neurological profiles not usually found in 8p23.1 DS. The clinical significance of three further 8p23.1 microduplications was uncertain due to additional genetic factors without which the probands might not have come to medical attention. Variable expressivity was indicated by the almost entirely unaffected parents in all five families and the mildly affected sibling in one. Intronic interruptions of six genes by microduplication breakpoint intervals had no apparent additional clinical consequences. Our results suggest that 8p23.1 DS is an oligogenetic condition largely caused by the duplication and interactions of the SOX7 and GATA4 transcription factors. © 2015 Wiley Periodicals, Inc.